2009
DOI: 10.1016/j.juro.2009.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Fournier's Gangrene: Population Based Epidemiology and Outcomes

Abstract: Purpose-Case series have shown a Fournier's gangrene mortality rate of 20% to 40% with an incidence of as high as 88% in some studies. Because to our knowledge there are no population based data, we used a national database to investigate the epidemiology of Fournier's gangrene.Materials and Methods-We used the State Inpatient Databases, the largest hospital based database available in the United States, which includes 100% of hospital discharges from participating states. Inpatients diagnosed with Fournier's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
239
5
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(259 citation statements)
references
References 14 publications
10
239
5
5
Order By: Relevance
“…Mortality rate was reported as 16% in a study including 1726 FG patients. [6][7][8] FG is a polymicrobial process starting with a triggering event. In etiology, both aerobic and anaerobic microorganisms play role.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality rate was reported as 16% in a study including 1726 FG patients. [6][7][8] FG is a polymicrobial process starting with a triggering event. In etiology, both aerobic and anaerobic microorganisms play role.…”
Section: Discussionmentioning
confidence: 99%
“…It is a rare disease 2,3 that predominantly affects males (at a 10 to 1 ratio) with an average age of 50 years. 2,4 Several predisposing factors have been identified: diabetes, alcoholism, arterial hypertension, renal and hepatic insufficiency, obesity, dementia, tobacco consumption and diseases that affect the immune system such as human immunodeficiency syndrome (HIV), chemo and radiotherapy, cancer and surgical interventions.…”
Section: 2mentioning
confidence: 99%
“…Early series reported high mortality rates around 80%in one report as high as 88% [21] but more recent studies have lower rates of mortality less than 40%. Barreda et al has reported a mortality rate of 29% in their retrospective case avalysis consisting of 41 patients [10]; on the other hand Sorensen et al has reported the overall case fatality rate was 7.5% in their large retrospective analysis including 1680 patients [3]. One of the most important measures for decreasing mortality and hospital stay is the timing of surgery.…”
Section: Managementmentioning
confidence: 99%
“…However the first description is known to be made by Baurienne in 1764 [1,2]. Despite advances in treatment; overall mortality remains high [3][4][5].…”
Section: Introductionmentioning
confidence: 99%